The inhibitory effect of vanadium oxoanions on the activity of copper-zinc superoxide dismutase - Apella, María Cristina (1988)
The inhibitory effect of vanadate species on the enzymatic activity of bovine copper-zinc superoxide dismutase has been investigated at different pH values and vanadium concentrations. A definite inhibitory effect, clearly related to the main negative charge of each of the vanadate solutions, has been found. The results suggest that the origin of the inhibitory effect may be similar to that found for the phosphate ion, i.e., a diminution of the effectiveness of the substrate electronic guidance mechanism by partial neutralization of the charges close to the active site. Under physiological conditions, the inhibitory effect of vanadate is somewhat smaller than the phosphate.